"COVID-19 made me a single parent" : an interpretative phenomenological analysis of a woman's perinatal experiences during the COVID-19 pandemic - Hadebe, Asanda Locresia (Rhodes University, Faculty of Humanities, Department of Psychology)
The COVID-19 pandemic resulted in unprecedented challenges across various aspects of life. In particular, pregnant women encountered unique challenges and circumstances that necessitated adaptation to the experience of the perinatal period1 Satyanarayana et al., (2011). A considerable amount of research has been conducted regarding women's experience of the perinatal period during COVID-19, especially in first world countries. However, inadequate research has been done in the South African context and specifically, there is a lack of qualitative research providing thick descriptions of experience. The analysis describes three master themes supported by subordinate themes. The main themes are (1) A sense of loss and change, (2) Managing COVID-19 and its regulations during the perinatal period, and (3) Glimmers of hope and desirable aftermaths. The study's findings expand and support the growing literature of women's experiences on the perinatal period during the COVID-19 pandemic.
Keywords: Perinatal care; COVID-19 Pandemic, 2020- Influence; Interpretative phenomenological analysis; Pregnant women -- South Africa; Pregnancy Psychological aspects; Psychology Qualitative research -- South Africa